O jeito do corpo e o jeitinho Brasileiro - Borges, Fernanda Carlos (2005)
In this dissertation, the jeitinho brasileiro is seen as a communication attitude which starts in the body, and it is investigated according to two aspects: the cognitive and the cultural. We understand the Way as a cognitive and communicative process, rooted in Brazilian culture through the jeitinho brasileiro. The Way takes us to the relationship between the universal and the particular, a basic theoretical structure developed during the historical patriarchy to hold the stability, which can be reached through cognitive capacity, and the unstable aspect experienced in the immediate relationship contingencies, in the body s relation with nature. In this system, the unstable aspect the body experiences under the circumstances should be beaten by the stability provided by the exactness of cognition. In this structure, communication has a persuasive aspect. However, another tradition has been conquering important space since the 20th century. This other tradition proposes that cognition is attached to continuous transformation, which suggests a change in the philosophy mainstream. The hypothesis that the Way corresponds to the shape communication takes in the forces of situation, is developed inside a tradition that corresponds to pre-patriarchal societies. The communication characteristic of this tradition is alterity. This thesis shares the position that the mind is basically embodied; the philosophy process is linked to the sensory-motor system of the human body. This line accepts a universal approach of what mankind is like, but also demands an understanding of the singular process of human life. The conception that human is equal according to the law characterizes the institutions of the countries in the Northern Hemisphere. In Brazil, this conception is enriched by the conception of equality considering the human condition. This is a substantial, body-related, equality that values understanding the forces of circumstances, compassion, and communicative capability. Therefore, the jeitinho brasileiro targets the perception of cultural, social and human processes and structures, which are different from those that support modern institutions, to which it doesn t submit. In order to consolidate this proposal, two thinkers were fundamental: José Ângelo Gaiarsa and Oswald de Andrade. Moreover, Lívia Barbosa s support was also very important.